(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2014)
يهدف البحث إلى دراسة واقع التخطيط الاستراتيجي في التعليم المهني والتقني ودوره في تحقيق احتياجات سوق العمل. حيث اعتمد البحث على المنهج الوصفي التحليلي, وتمّ توزيع (314) استمارة على الإداريين والمدرّسين في مدارس التعليم المهني والتقني في محافظة اللاذقية, وباستخدام الأساليب الإحصائية المناسبة كان من أهم نتائج البحث: 1- يتسم التعليم التقني والمهني بنقاط ضعف تقلل من كفاءته, ويظهر ذلك في عدم متابعة مدرسة التعليم المهني لخريجيها, وعدم توافر نظام تأمين ضدّ الحوادث للمدرّبين المعلّمين في ورش ذات خطورة عالية, وضعف المناهج من حيث قدرتها على تأهيل الطالب للدخول إلى سوق العمل. 2- تعاني التجهيزات المتوافرة في التعليم التقني والمهني من ضعف تجهيزها بوسائل وتجهيزات الأمن والسلامة المهنية المتطوّرة, كما أن المختبرات والورش والمشاغل غير كافية, ولا تراعى المقاييس والمعايير التي تتلاءم مع طبيعة التخصصات المتوفّرة فيها عند تجهيز الأبنية. 3- هناك ضعف واضح في دور التعليم المهني والتقني في تحقيق احتياجات سوق العمل على الرغم من وجود تشريعات وقوانين تؤهله للاضطلاع بدوره في تنمية مهارات العمل, ويظهر ذلك من خلال عدم تشجيع القطاع الخاص لإقامة مشروعات التعليم التقني والتدريب المهني, وعدم تعزيز مشاركة المجتمع المحلي في إدارة وتمويل التعليم التقني والمهني بما يحقق التوأمة بين مناهج وبرامج التدريب ومتطلبات خطط التنمية الاقتصادية, وضعف تأهيل الكفاءات البشرية التقنية والتعليمية والإدارية لمواكبة المستجدات والتطور التقني. The research aims to study the reality of strategic planning for vocational and technical education and its role in achieving the needs of the labor market. The research uses the descriptive analytical method. 314 forms were distributed to administrators and teachers in the schools of vocational and technical education in the Province of Latakia. Using appropriate statistical methods, the research comes up with some important results: • Weaknesses of technical and vocational education reduce its efficiency. This is reflected in the lack of any follow-up programs or any contact of school vocational education with their graduates; and the unavailability of a system accident insurance for trainers and teachers in high-risk workshops; and the weakness of the curriculum in terms of its ability to rehabilitate the student to enter the labor market. • The equipment available in technical and vocational education is not well-looked and safety standards are not high and in laboratories and workshops and do not fit with the nature of the disciplines. • There are obvious weakness in the role of vocational and technical education in achieving the needs of the labor market, despite the existence of legislation and laws to qualify it to carry out its role in the development of work skills. This is evident in discouraging the private sector from setting up projects of technical education and vocational training as well as in the absence of community participation in management and financing of technical and vocational education. Therefore, is important to twin between the curricula and training programs and the requirements of economic development plans. There is also the need to keep up with technological developments.